Robotic duodenum-preserving pancreatic head resection with preoperative three-dimensional visualization and intraoperative real-time indocyanine green fluorescence navigation - Yaqiang Shu; Chuanfu Li; Bo Liu; Fan Wu; Chao Zhang; Muyu Fu; Xiaohua Lei; Guodong Chen (Intelligent Surgery)
Duodenum-preserving pancreatic head resection (DPPHR) has been widely used in benign tumors, low-grade malignant tumors of the pancreatic head and chronic pancreatitis. Nevertheless, to date, there has been no report about indocyanine (ICG) fluorescence in robotic DPPHR. This report describes the technique of robotic DPPHR with preoperative three-dimensional reconstruction visualization and intraoperative real-time ICG fluorescence imaging navigation. The results show that the technique is safe and effective for benign masses of the head of the pancreas and may offer a benefit for maintaining the integrity of duodenal blood flow and the biliary system.